(untitled) (Bangladesh Journal of Pharmacology, 2015)
Uricosuric activity of different extracts of Tinospora cordifolia was studied in hyperuricemia induced in albino Wistar rat using potassium oxonate. The uric acid level in serum and urine were measured. Uricosuric activity was also evaluated using phenol red dye excretion model. Phenol red levels were measured in blood. In potassium oxonate induced hyperuricemia, probenecid, aqueous, hydro-alcoholic, dichloromethane extract and galo satwa (starch of T. cordifolia) significantly lowered the serum uric acid levels. All the extracts increased uric acid excretion and decreased the elevated serum uric acid levels induced due to potassium oxonate. Probenecid, aqueous extract and galo satwa significantly increased fractional excretion of uric acid and phenol red levels in blood indicating uricosuria. Polysaccharides in aqueous extract and galo satwa may be responsible for uricosuric action. Video Clips of Methodology: Preparation of extracts 4 min 22 sec Prepared extracts 26 sec Potassium oxonate induced hyperurecimia 1 min 46 sec Injection of red phenol into tail vein 52 sec Collection of blood 16 sec Estimation of uric acid 1 min 44 sec